Supporting struggling students on placement : a practical guide - Finch, Jo (Policy Press shorts. Policy & practice., 2017)
Practical guidance that will further knowledge and engender confidence for any teachers, assessors and supervisors on courses with a practice learning component, based on the authors first-hand experience and international multi-disciplinary research and literature.